The Mechanisms of the Transportation Land Transfer Impact on Economic Growth: Evidence from China - Mingzhi Zhang; Zhaocheng Li; Xinpei Wang; Jiajia Li; Hongyu Liu; Ying Zhang (Land, 2021)
Accessibility to transportation is a crucial factor for economic growth. Transportation land, defined as the land used to support transportation infrastructure, such as city and inter-city rail, ports, and air travel, is a critical element for constructing transportation facilities and has attracted increasing attention from researchers and policy makers. Transportation land transfer (TLT) is defined as the act by which the state transfers transportation land-use rights to a land user (collective or individual) within a certain period of time as the land owner (all land in China is owned by the state). The land user pays a land-use right transfer fee to the state. This article first reveals the multidimensional effect between TLT and economic growth based on data from China’s 30 provinces for 2007–2019. The study found the following. (1) A continuous increase in the availability of transportation land is vital to ensure sustainable economic growth, and the construction of transportation land between adjacent areas has positive spatial spillover effects. (2) These positive effects work through three mechanisms, i.e., increased employment, industrial interactions, and improvements in economic operational efficiency, with a time lag. (3) The positive effects of TLT on economic growth have significant heterogeneous moderating effects on the differences in the economic development stage, the level of industrial structure, and urbanization rate. The study expands the front-end to back-end analysis of land use, provides a reference for countries and regions at different stages of development to promote economic growth using transportation land construction, and presents beneficial insights for governments to efficiently avoid the mismatch of transportation land resources.